Pharmacogenetics of stavundine : role of genetic variation in mitochondrial DNA and polymerase gamma among adult Malawian HIV/AIDS patients - Kampira, Elizabeth (Department of Clinical Laboratory Sciences, 2014)
Includes abstract.